Capillary collagen as the physical transport barrier in drug delivery to tumor microenvironment - Ziemys, Arturas (Tissue Barriers, 2015)
The capillary wall is among the most important barriers that controls mass exchange between tumor microenvironment and systemic circulation. There are numerous studies on endothelial cells role in this mass exchange, but the role of capillary collagen of Type-IV in transport of small molecules and nanotherapeutics is less known. Our recent study revealed that the capillary wall collagen modulates the drug transport across the wall, and that it can be taken as a biophysical marker for drug transport. In our in vivo investigations with the 3LL and 4T1 tumors we noticed the differences in the collagen content in capillary walls. The imaging analysis and transport computational model of the capillary microenvironment showed that the penetration of doxorubicin (DOX) and pegylated liposomal doxorubicin (PLD) is substantially reduced by larger collagen content in the capillaries of the 3LL tumors. The results pointed to the importance of transport oncophysics, which opens a new avenue with respect to classical biology in understanding and improving drug delivery by nanotherapeutics, and aims to better explain the therapeutic resistance.